Constructing Moral Expectations and Social Recognition: A Qualitative Case Study of Santri and Non-Santri in Jogowono - Afifah, Auliana; Nasir, Mahmud (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Religious education can create moral expectations toward individuals associated with Islamic educational institutions, but educational identity does not necessarily determine how their conduct is evaluated in community life. This study examines how five selected informants in Jogowono perceived the akhlak (Islamic moral character) of santri and non-santri, identifies the factors informing those perceptions, and analyzes their social construction using Berger and Luckmann’s framework. The study employed a qualitative case study design. Data were collected from two community leaders, one kiai, one santri, and one non-santri through semi-structured interviews, moderate participant observation, and document analysis. The data were coded thematically and interpreted through the processes of externalization, objectivation, and internalization. The findings show that santri identity generated higher initial moral expectations because it was associated with more intensive religious education. However, the informants accorded moral recognition primarily on the basis of observable conduct, including respectful communication, responsibility, cooperation, social concern, and participation in religious and community activities. Their evaluations were informed by religious education, family environment, social environment, and lived social interaction. Externalization occurred through participation in communal practices, objectivation through the formation of shared expectations surrounding santri identity, and internalization through individuals’ acceptance or negotiation of those expectations. The study provides a context-specific distinction between moral expectations attached to religious educational identity and social recognition earned through everyday conduct. Its findings represent the perspectives of the five informants and do not establish that either educational background produces superior moral character.